Influence of water level variation on biomass and chemical composition of the aquatic macrophyte Eichhornia azurea (KUNTH) in an oxbow lake of the Rio Mogi-Guaçu (São Paulo, Brazil) - Camargo, A. F.M. [UNESP]; Esteves, F. A. (My University, 1996)
The influence of water level variation (flood pulse) on the biomass and chemical composition of the aquatic macrophyte Eichhornia azurea, was investigated in a tropical oxbow lake of the Rio Mogi-Guaçu, State of São Paulo, Brazil. The flood pulse causes an increase in total nitrogen content from 0.67 to 1.35mg/L and total phosphorus content from 10.5 to 101.0 μg/L of the water. This fertilization, associated with other factors, determines a typical seasonal variation in the biomass and chemical composition of the macrophyte.